Peran Perangkat Pembelajaran dalam Menjamin Mutu dan Arah Pembelajaran di Perguruan Tinggi - mardin, La Ode; Sukiman (Al-Riwayah : Jurnal Kependidikan, 2025)
Learning tools are strategic elements in the implementation of higher education, as they form the foundation for designing, implementing, and evaluating quality teaching and learning processes. This study aims to comprehensively examine the role of learning tools in ensuring the quality and direction of learning in universities. This research uses a literature review method by analyzing various sources, including academic journals, textbooks, national education policies, and other relevant articles. The results show that learning tools which consist of Semester Learning Plans (RPS), teaching materials, and instructional media must be developed systematically, integratively, and in alignment with graduate learning outcomes (CPL). RPS serves as the main reference in designing learning activities; teaching materials support the substantial achievement of competencies; and instructional media enhance the effectiveness of content delivery. Inconsistencies or weaknesses in any component may lead to disorganized learning processes and low-quality learning outcomes. Therefore, it is essential to improve lecturers’ capacities in preparing standardized and adaptive learning tools. In addition, institutional support through training, mentoring, and evaluation systems is necessary to ensure the sustainability of higher education quality. These findings confirm that learning tools are not merely administrative documents, but a critical factor in ensuring the direction, effectiveness, and success of the educational process in higher education institutions.